Exploring nurses’ experiences in applying AIDET framework to improve communication skills in the emergency department: A qualitative study - Werapol Panchuay; Thassanee Soontorn; Praneed Songwathana (Belitung Raya Foundation, Indonesia, 2023)
Background: Recognizing the significance of effective communication in raising emergency department service standards and preventing misinterpretation of patient needs among registered nurses is crucial for improving patient satisfaction. The utilization of the AIDET (Acknowledge, Introduce, Duration, Explanation, and Thank you) communication framework is acknowledged to enhance communication among registered nurses, patients, family members, and other healthcare professionals. Objective: This study aimed to explore Thai nurses’ experiences in applying the AIDET framework for communications with patients and their relatives in the emergency department. Methods: A qualitative descriptive research design was employed. Semi-structured interviews with 15 emergency nurses were conducted between September and March 2022 in a regional hospital in Thailand. Data were analyzed using content analysis. Results: Three themes were generated: 1) Ability to follow the AIDET framework, 2) Recognizing the value of using AIDET steps for positive communication, and 3) Establishing a foundation for successful communication. Conclusion: The study’s findings highlighted the AIDET framework’s potential to enhance communication skills between nurses, healthcare professionals, and patients. The results also emphasized the importance of providing training and mentorship to junior nurses, integrating AIDET into daily routines and institutional policies, and facilitating continuous education for registered nurses. These efforts contribute to improving care quality and aligning with patient and family needs.